ALMA MATER IN THE YEAR OF ITS 70TH ANNIVERSARY - Aleksey V. Pavlov (Высшее образование в России, 2016)
In 2014 Yaroslavl State Medical Academy celebrates the 70th anniversary. Academywas found in 1944 in the days of II World War and since that time plays an important role in the system of higher medical education in our country and in educational, scientific and social life of Yaroslavl region. Today Yaroslavl State Medical Academy is the large educational andscientific center with adeveloped imageof reliable business andsocial partner. The article describes main features of educational system, including practical training on the different education levels, employment assistance system, clinical research and scientific school development, innovative pedagogical technologies, student extracurricular cultural activities, management system and development potential.